CYP6B Subtype Expression Fluctuates in the Great Mormon, Papilio memnon, with Changes in the Components of the Host Plants - Miho Nakano; Takuma Sakamoto; Yoshikazu Kitano; Hidemasa Bono; Hiroko Tabunoki (Insects)
Cytochrome P-450 (CYP) is one of the metabolic enzymes which is conserved among organisms to metabolise xenobiotics. The metabolic role and transcriptomic profiles of the CYP6B subfamily have been studied in some Papilionidae insects. However, the role of CYP6Bs expressed in Rutaceae plant-fed swallowtails has yet to be fully examined. Here, the expression profile of CYP6B in the Great Mormon (Papilio memnon) larvae, which prefer Citrus plants to the Rutaceae plant, was investigated by RNA sequencing analysis and real-time quantitative PCR when feeding different kinds of Citrus plants. We found that six kinds of CYP6B subtype transcripts were expressed in the larval fat body and midgut. Then, we focused on CYP6B2, CYP6B5, and CYP6B6 transcripts and examined their mRNA expression in the larvae fed on different plants. These CYP6B mRNA expressions were changed in the larval fat body and the midgut by changing the host plants. The presence of chemicals specific to each host plant was confirmed when the host plant components were examined by database, literature, and thin-layer chromatography. Our study suggests that phytochemicals in the host plant affect CYP6B subtypes mRNA expression in P. memnon larval fat body and midgut, and CYP6B subtypes may relate to metabolise the phytochemicals in the host plants.